Research on Resistance to Sulfate and Chloride of Reinforced Metakaolin-Based Geopolymers - Aygormez, Yurdakul; Canpolat, Orhan (UNIV TUN HUSSEIN ONN MALAYSIA, 2022)
This research aims to examine the sulfate and chloride durability behaviors of geopolymer composites synthesized by the alkali activation of metakaolin (MK), reinforced by boron waste colemanite (C), silica fume (SF), and slag (S). The resultant geopolymer composites were subjected to magnesium sulfate (MgSO4) solution (concentration 10%), sodium sulfate (Na2SO4) solution (concentration 10%), and sodium chloride (NaCI) solution (concentration 10%) for up to 12 months. The compressive and flexural strengths, microstructure (X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM)), weight changes, and visual inspection of the geopolymer composites were investigated to evaluate their durability behavior. The conclusion proved that the mix of a metakaolin with the addition of 10% C, and 20% SF shows the highest compressive strength for the studied range of mixture design. In geopolymer mortar samples, compressive strength increase was observed due to sodium chloride and sodium and magnesium sulfate effects after three months, while a decrease was observed after six months. These fluctuations were due to the diffusion of solutions in the matrix, formed during the transition of alkali ions from the samples to the solution. The loss of strength after three months could be due to the presence of microcracks, as a consequence of ettringite and gypsum creation in the pores, as well as the transition of alkalis from the sample matrix to the solution.
Keywords: Geopolymer; metakaolin; colemanite waste; silica fume; magnesium sulfate; sodium sulfate; sodium chloride; FLY-ASH; PARTIAL REPLACEMENT; RED MUD; DURABILITY; ATTACK; MORTARS; SODIUM; MICROSTRUCTURE; PERFORMANCE; COMPOSITES; Construction & Building Technology